Autism: a missing protein in brain? - Hemaila Shanzeh Tariq; Muhammad Yusuf Hafiz (Journal of the Pakistan Medical Association, 2021)
Autism Spectrum Disorder is a set of neurodevelopmental disorders characterized by deficits in social communication (social-emotional reciprocity, non verbal interaction and developing and maintaining relationships) and restricted and repetitive behavioral patterns or interests.1 Autism is a multi-factorial, rather than single, disorder of complex etiology. Continuous....